Language's Units in contemporary Poetry - محمد خسروی شکیب (مطالعات زبانی و بلاغی)
Contemplation and meaning occurred on surface of âlanguage, so that it has deep and surface levels. Discovery âand analysis of meaning needs to survey and precisely been âanalyzed over deep and surface structure of language. âFragmentation and misconstruction surface the discovery of âsing with slow going. Poetry is a creative phenomenon so that âhas been made consciously and unconsciously. Necessity of âsearching of language will be acceptable because of âunderstanding and discovering the deep meaning of verse.â Three units of language â words, sentence and stanza- âhas been discovered and discussed by this proper and this will âshow the identity and independence of contemporary poetry. â